Measurement of bioactive trace metals (Cu and Zn) in the Southern Ocean : validation of sampling protocol and ICP-MS based analytical method - Cloete, Ryan (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.